181k views
3 votes
Pls help me with this question

Pls help me with this question-example-1
User Komengem
by
4.5k points

2 Answers

6 votes

Answer:


\huge{ \boxed{ \bold{ \tt{x = 1}}}}

Option C is correct.

Explanation:


\text{First ,\: let's \: know \: about \: exponential \: equation} :

Exponential Equation

An equation in which variables appears as an exponent of a base is known as exponential equation. The following axioms are useful while solving the exponential equations :

  • If
    \sf{ {a}^(x) = {a}^(b) } , then x = b
  • If aˣ = 1 , then aˣ = a⁰ and x = 0

Thus , while solving an exponential equation, we should simplify the equation till the equation is obtained in the form
\sf{ {a}^(x) = {a}^(b)} or aˣ = 1 .

Now, let's start to solve :


\sf{ {2}^((9x - 3)) = {8}^(( 3 - x))}


\sf{ {2}^(9x - 3) = {2}^(3(3 - x)) }


\sf{ {2}^(9x - 3) = {2}^(9 - 3x)}


\sf{ \cancel{2} ^( \: 9x - 3) = \cancel{2} ^( \: 9 - 3x) }


\sf{9x - 3 = 9 - 3x}


\sf{9x + 3x = 9 + 3}


\sf{12x = 12}


\sf{ (12x)/(12) = (12)/(12)}


\boxed{ \sf{x = 1}}

The value of x is 1 .

Hope I helped!

Best regards! :D

~
\text{TheAnimeGirl}

User Andrew Seguin
by
5.0k points
1 vote

Answer:

option C, x=1

Explanation:


2^(9x-3) = 8^(3-x)


2^(9x-3) = (2^3)^(3-x)


2^(9x-3) = 2^(9-3x)

cut 2 from LHS and RHS you will get,

9x-3 = 9-3x

9x + 3x = 9 + 3

12x = 12

x = 12/12

x = 1

therefore, option C is the correct option

hope it helps you!

User Eestein
by
5.3k points